A molecular understanding of Alzheimer's disease - Hardy, John (Henry Stewart Talks, 2007)
Usefulness of genetics in understanding AD, Pathology of diseases, Amyloid protein, Genetic maps, Mechanism of late onset Alzheimer's, Role of presenilin in amyloid pathology, Tau and frontotemporal dementia, Tau splice site mutations, Pathways to neurodegeneration
Updated at 2021/03/08